Protease activity in Giardia duodenalis trophozoites of axenic strains isolated from symptomatic and asymptomatic patients - Guimarães, Semíramis [UNESP]; Sogayar, Maria Inês Terra Leme [UNESP]; Franco, Marcello Fabiano (Instituto Oswaldo Cruz, Ministério da Saúde, 2003)
We have examined by gelatin-SDS-PAGE the protease activity in cell lysates of Giardia duodenalis trophozoites of two axenic strains isolated in Brazil from a symptomatic patient (BTU-11) and an asymptomatic carrier (BTU-10), and the reference strain Portland 1 (P1). The proteolysis band patterns showed differences among strains isolated from asymptomatic and symptomatic individuals. The lysate of the strain BTU-10, showed only five hydrolysis bands, while a greater number of bands (10-11 bands) was seen in strains BTU-11 and P1. The protease activity in all lysates was inhibited by cysteine (E-64 and iodoacetamide) and serine proteases (TPCK and TLCK) inhibitors, but not by PMSF and EDTA. In general, the results revealed protease activities in G. duodenalis trophozoites of Brazilian axenic strains and the predominance of cysteine proteinases. It should be stressed the inter-strain difference in hydrolysis band patterns observed between strains isolated from symptomatic patients and the strain obtained from an asymptomatic carrier.
Keywords: Giardia duodenalis; axenic strain; trophozoites; protease activity